Analisis Cemaran Logam Timbal Dalam Teh Hijau (Camellia Sinensis) Dan Teh Hitam (Camellia Sinensis (L.) O. Kuntze) Secara Destruksi Basah Dan Kering - Kurnia Nur Indah; Nuraini Harmastuti; Vivin Nopiyanti; Suhartinah Suhartinah; Widodo Priyanto (Jurnal Farmasi Indonesia, 2025)
Tea (Camellia sinensis) is an easily oxidised herbal plant with cardiotonic, diuretic and astringent properties. Pb in tea occurs due to vehicle pollution, waste and garbage disposal. This study aims to determine the levels of heavy metal lead (Pb) contamination in green and black tea and determine wet and dry methods for analysing samples. This study uses experimental laboratory type including the collection and preparation of green tea and black tea samples, making standard curves, determining the variation of oxidising agents HNO3 and H2SO4 with a ratio of (3:1). Testing using Absorption Spectrophotometry. The results showed the highest level in home industry A sample A1 green wet 1.4 mg/kg and the lowest level of sample A3 black wet 1.07 mg/kg. The highest level of home industry B sample B3 black wet 1.2 mg/kg and the lowest level of sample B1 green wet 1.1 mg/kg. Both samples met the requirement of ≤ 2 mg/kg.